ANALISIS PERLINDUNGAN HUKUM INVESTOR TERHADAP PERUSAHAAN INVESTASI DALAM HAL GAGAL BAYAR (DEFAULT) - Muhammad Fauzi Rais; Rosewitha Irawaty (Jurnal Education and Development, 2022)
Recently, there have been several cases of default that have caused unrest in the community, one of which is that the Investment Company, the State and OJK have an important role in supervising and protecting the law and its various regulations. In view of this default, it is important to avoid and to prevent the same case and also to provide special protection to investors. This study aims to analyze the responsibilities of investment companies and examine and examine more deeply how the legal protection for investors. The research method used in this research is normative juridical and analytical descriptive research, namely by solving the problem being investigated by describing the current state of the research object based on visible facts, which is then analyzed through applicable regulations. The results of the study show that investment companies in the event of default (default) Investor protection is needed in the form of information disclosure, and also the existence of collateral (collateral) accompanied by the existence of reserve funds or known as sinking funds. Apart from that, preventive and repressive legal protection as well as the application of sanctions that are up to date are deemed necessary to be presented from the Laws and Regulations of the Financial Services Authority (POJK). because it is an institution that has the authority to protect investors' legal rights, so that in the future there will not be a similar case in case of default, because investors get rights and legal protection.